Advancing Peripheral Nerve Graft Transplantation for Incomplete Spinal Cord Injury Repair - Kjell, Jacob; Svensson, Mikael (Frontiers in Cellular Neuroscience, 2022)
Peripheral nerves have a propensity for axon growth and regeneration that the central nervous system lacks (CNS). However, CNS axons can also grow long distances if introduced to a graft harvested from a peripheral nerve (PNGs), which is the rationale for using PNGs as repair strategy for injuries of the spinal cord. From a clinical perspective, PNGs provide interesting possibilities with potential to repair the injured spinal cord. First, there are numerous options to harvest autologous grafts associated with low risk for the patient. Second, a PNG allow axons to grow considerable distances and can, by the surgical procedure, be navigated to specific target sites in the CNS. Furthermore, a PNG provides all necessary biological substrates for myelination of elongating axons. A PNG can thus be suited to bridge axons long distances across an injury site and restore long tracts in incomplete SCI. Experimentally, locomotor functions have been improved transplanting a PNG after incomplete injury. However, we still know little with regard to the formation of new circuitries and functional outcome in association to when, where, and how grafts are inserted into the injured spinal cord, especially for sensory functions. In this perspective, we discuss the advantages of PNG from a clinical and surgical perspective, the need for adding/repairing long tracts, how PNGs are best applied for incomplete injuries, and the unexplored areas we believe are in need of answers.